Long‐Range Nonvolatile Electric Field Effect in Epitaxial Fe/Pb(Mg1/3Nb2/3)0.7Ti0.3O3 Heterostructures. (3rd April 2018) - Zhou, Cai; Shen, Lvkang; Liu, Ming; Gao, Cunxu; Jia, Chenglong; Jiang, Changjun; Xue, Desheng
Abstract: One of the ideal candidates of using electric field to manipulate magnetism is the recently developed multiferroics with emergent coupling of magnetism and electricity, particularly in synthesizing artificial nanoscale ferroelectric and ferromagnetic materials. Here, a long‐range nonvolatile electric field effect is investigated in Fe/Pb(Mg1/3 Nb2/3 )0.7 Ti0.3 O3 heterostructure using the dependence of the magnon‐driven magnetoelectric coupling on the epitaxial Fe thin film (4–30 nm) thickness at room temperature using measurements based on the ferromagnetic resonance. The magnon‐driven magnetoelectric coupling tuning of the ferromagnetic resonance field shows a linear response to the electric field, with a resonance field shift that occurs under both positive and negative remanent polarizations, and demonstrates nonvolatile behavior. Moreover, the spin diffusion length of the epitaxial Fe thin film of ≈9 nm is obtained from the results that the change of the cubic magnetocrystalline anisotropy field under different electric fields varies with Fe thickness. These results are promising for the design of future multiferroic devices. Abstract : A long‐range nonvolatile electric field effect is investigated in Fe/Pb(Mg1/3 Nb2/3 )0.7 Ti0.3 O3 heterostructures using the dependence of the magnon‐driven magnetoelectric coupling on the epitaxial Fe thin film (4–30 nm) thickness measured by ferromagnetic resonance. Moreover, a spin diffusion length of the epitaxial Fe thin film of ≈9 nm is obtained. These results are promising for the design of future multiferroic devices.